Inovasi Pengendalian Keuangan: Memperkuat Kinerja Siklus Murabahah KSU Kota Santri Bojong - Windy Fatmawati; Gunawan Aji (Jurnal Akuntansi dan Audit Syariah)
KSU Kota Santri Bojong has Murabahah products that are of interest to the community. This financing has operational standards that have been set by the internal organization. However, whether the standard has been implemented as it should. This internal control test aims to determine the extent to which the internal control system is operating. Includes activities of applying as a cooperative member, financing application, verification, financing, installments and repayment. Researchers used adopt observation, interview and documentation methods. Researchers used internal control questions to obtain reinforcing and comparative data. Triangulation is the basis for interpreting the analysis of comparing field facts with standards that should be. The results of this study state that the Murabahah cycle standards have been carried out, but still need improvement. Through the murabahah accounting information system described and field documentation related to the treatment of each stage of the murabahah cycle. KSU Kota Santri faces various challenges, one of which is the separation of functions and digitalization of the murabahah system. Some stages of Murabahah still depend on manual methods, so KSU Kota Santri needs an update that is more effective, efficient, complex and economical.